Manejo de azevém (Lolium multiflorum Lam.) resistente ao glyphosate com o uso de diferentes herbicidas - Stasievski, Angelo [UNESP] (2015)
The overall objective of this study was to evaluate management alternatives ryegrass resistant to glyphosate, by using ACCase inhibitors, photosystem I, and glutamine synthetase in three distinct growth stages (tillering, booting and early flowering ), as well as the effect of sequential application of paraquat, and the residual effect (carry-over) of these herbicides to corn. For the information required, it was conducted three studies, and the Study 1 aimed to characterize or define the degree of resistance of ryegrass population to glyphosate, when the herbicide was applied at different growth stages. The Study 2, aimed at verifying the effectiveness of different herbicides in controlling the resistant ryegrass to glyphosate. The Study 3, aimed to determine the potential for phytotoxicity of ACCase inhibitor herbicide to corn when applied 0, 5, 10 and 15 days prior to sowing, in both soils, sandy clay loam and clay. In the first study, it was determined the resistance factor (RF) of the glyphosate-resistant ryegrass population in experiments of dose response curves. The treatments consisted in the application of glyphosate at doses: 0, 45, 90, 180, 360, 720, 1440, 2880, 5760, and 11520 g a.e.ha-1, on susceptible and potentially resistant ryegrass populations, in three phenological stages. The second study consisted of three experiments and was aimed to evaluate the herbicidal effect on the management of ryegrass applied in three distinct stages, as well as the effect of sequential application of paraquat (300 g a.i.ha-1). The treatments consisted of glyphosate at 1080, 1440 and 1800 g a.i.ha-1; clethodim: 72, 96 and 120 g a.i.ha-1; tepraloxydim: 75, 100 and 125 g a.i.ha-1, haloxyfop-p-methyl: 45, 65 and 75 g a.i.ha-1, quizalofop-p-ethyl: 56.25, 75 and 93.75 g a.i.ha-1, fluazifop-p-butyl: 187.5; 250 and 312.5 g a.i.ha-1, paraquat: 225, 300 and 375 g a.i.ha-1; gluphosinate: 300, 400 and 500 ...